Contribution of Parents' Support to Adolescent Attitudes About Free Sex Behavior - Nala Satriana; Herman Nirwana; Syahniar Syahniar (International Journal of Applied Counseling and Social Sciences, 2020)
Free sex in Indonesia from time to time is very worrying. Teenagers think free sex is a normal and normal thing to do. Adolescent attitudes affect the behavior carried out. This study reveals the contribution of parental support to adolescent attitudes about free sex behavior. This research uses the correlational method and data collected from a sample of 235 students, which were found using proportional random sampling techniques. Data were collected using a parental support scale (32 valid items, = 0.873), and a scale of adolescent attitudes about free sex (22 valid items = 0.885). Data were then analyzed using multiple regression. The results show that parental support contributed 17.9% to adolescent attitudes about free sex behavior. It can be concluded that the higher the parental support, the adolescent’s items, about free sex will be more negative.